1984
DOI: 10.3354/meps018119
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of meiobenthic grazing rates on sediment bacteria and edaphic diatoms

Abstract: A radioactive tracer technique was used to measure meiofaunal grazing on bacteria and diatom communities in natural sediments. Radioactive '4C-glucose and 14C-bicarbonate were used to label heterotrophs (bacteria) and autotrophs (diatoms), respectively. The labeled compounds were added to undisturbed sediment cores and incubated for 4 h at in situ temperatures. After incubation, radioactivity was determined for the sediment (microbes) and the major meiofaunal taxa. To quantify meiofaunal grazing on microbes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
5

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 49 publications
5
106
1
5
Order By: Relevance
“…These results are in agreement with bulk-isotope studies which have shown that planktonic and benthic algae are important contributors of carbon for the dominant meiofaunal taxa like nematodes, harpacticoid copepods and ostracods (e.g. Gleason & Zimmerman 1984, Montagna 1984, Riera et al 1996. In contrast, Couch (1989) reported 6I3C values for the meiofauna (-13.9 to -15%0) intermediate between the benthic algae (-12 to -13.5%0) and Spartina alterniflora detritus (-15.9 to -16.7%) and concluded that detrital S. alterniflora may be the main source of C for the meiofaunal populations in the North Inlet Estuary, South Carolina.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with bulk-isotope studies which have shown that planktonic and benthic algae are important contributors of carbon for the dominant meiofaunal taxa like nematodes, harpacticoid copepods and ostracods (e.g. Gleason & Zimmerman 1984, Montagna 1984, Riera et al 1996. In contrast, Couch (1989) reported 6I3C values for the meiofauna (-13.9 to -15%0) intermediate between the benthic algae (-12 to -13.5%0) and Spartina alterniflora detritus (-15.9 to -16.7%) and concluded that detrital S. alterniflora may be the main source of C for the meiofaunal populations in the North Inlet Estuary, South Carolina.…”
Section: Discussionsupporting
confidence: 81%
“…These three components are closely linked by numerous types of interactions and a vast literature concerning them exists, but only the relationships between macrofauna and meiofauna or between meiofauna and bacteria are commonly considered. In particular, the predation pressures of macrofauna upon meiofauna and, reciprocally, of meiofauna upon macrofaunal juveniles are well known (Bell and Coull 1980;Gee 1987) and there is also evidence of a regulatory impact of meiofauna upon bacteria (Montagna 1984;Nilson et al 1991). Furthermore, previous findings within the literature do not only suggest nutritional interactions or competition, but also the presence of some synergistic relationships (Tenore and Rice 1980;Reise 1985;Tita et al 2000).…”
Section: Introductionmentioning
confidence: 78%
“…In contrast, holothurians and other sediment-feeders feed on material and organisms spanning 3 orders of magnitude (approximately from bacteria <1 µm up to diatoms >1 mm), and thus their function in such a food web is very difficult to grasp. Generally, grazing on a microbial food source in the benthos may increase productivity by preventing bacteria from reaching self-limiting densities (Johannes 1965, Gerlach 1978, Montagna 1984. A similar mechanism was suggested for gastropod grazing on bacteria in temperate (Bianchi & Levington 1981 and coral reef sediments (Hansen & Skilleter 1994), and the feeding activity of detritivores may stimulate bacterial decomposition of detritus (Fenchel 1971, Kristensen et al 1992).…”
Section: Combined Positive and Negative Feedback Effectsmentioning
confidence: 99%
“…Montagna 1984, Moriarty et al 1985, Hansen & Skilleter 1994. The effects that grazers have on plant production are composed of negative feedback effects by consumption, and of a variety of potential positive feedback effects.…”
Section: Introductionmentioning
confidence: 99%